The demise of moderate Islam: new media, contestation, and reclaiming religious authorities - Wahyudi Akmaliah (IAIN Salatiga, 2020)
The landscape of the Indonesian public sphere amidst the rise of new media has opened both opportunities and threats dealing with Islamic teaching. This condition shapes a danger for the two largest of moderate Muslim Organisations (Muhammadiyah and Nahdatul Ulama/NU), in which they do not engage a lot of this development of the digital platform. Consequently, dealing with religious issues, their voices become voiceless. By employing desk research through some relevant references and collecting information from social media, specifically Instagram and Youtube, this article examines the role of the Islamic organization of moderate Islam in the rapid of the digital platform as the new of the public sphere. The article finds that they have difference respond to dealing with the presence of the new religious authorities. In comparison, while Muhammadiyah is more accepting of them calmly, NU is more reactively in responding.Lanskap ruang publik Indonesia di tengah muncunya media sosial membuka kesempatan sekaligus ancaman terkait dengan dakwah Islam. Hal itu merupakan ancaman bagi dua organisasi besar Moderat Islam di Indonesia (Muhammadiyah dan NU), di mana mereka menjadi kelompok minoritas dalam aktivitas dakwah online. Akibatnya, berkaitan dengan issu-isu keagamaan, suara mereka menjadi tidak terdengar/didengarkan. Dengan melakukan riset studi literatur yang relevan dan informasi yang didapatkan dari akun media sosial, khususnya Instagram dan Youtube, artikel ini menjelaskan peranan organisasi Islam moderat di tengah cepatnya platform digital di ruang publik. Artikel ini menemukan bahwa Muhammadiyah dan NU memiliki respon yang berbeda terkait dengan kehadiran otoritas keagamaan baru. Sebagai perbandingan, penerimaan Muhammadiyah terhadap kehadiran mereka terlebih lebih biasa ketimbang dengan NU yang reaktif.